CZAJKA’S MYTHOLOGIES - Tomczok, Marta (Porównania, 2019)
In this article I discuss the phenomenon of the mythology of a Polish-Jewish active artist in the second half of the twentieth century. This is a mythology of “long duration”, because it goes back to the interwar period, surrealism, avant-garde and Warsaw’s Bohemia. The example is provided by prose from Izabela Czajka Stachowicz but also statements of literary critics and journalists of Jan Kott, Krystyna Kolińska, and Ryszard Matuszewski. By means of discussing gender stereotypes and stigmas that the works of Czajka were described with after the war, I try to show the negative aspects of her mythology. In turn, I am looking for a reaction to stigmatization in the form of symbols of objects and animals in her prose.